PERAN PEMERINTAH KABUPATEN JEPARA DALAM RANGKA FASILITASI TERHADAP INDUSTRI MEBEL DALAM PERDAGANGAN BEBAS (Studi Kasus Berlangsungnya ACFTA) - Meily Murdiyani; Priyatno Harsasto; sulistyowati . (Journal of Politic and Government Studies, 2016)
The purpose of this research is to 1) know the role of the district government Jepara in facilitate for entrepreneurs furniture in Jepara after agreement ACFTA; and 2) know what factors to becoming an obstacle in facilitate entrepreneurs furniture in Jepara. This research inclined to descriptive qualitative, so that excavation data obtained off the subject research through technique interview deep, among others with the Head of Disperindag Jepara regency, Head Of Industry Disperindag Jepara regency. The results of the study shows the role of the district government Jepara in facilitate for entrepreneurs furniture in Jepara after agreement ACFTA done through a strategic approach, both through regulations and institutionalization. Approach regulations done to issue by law of Jepara regency number 2/ 2014 on the protection, empowerment, guidance industry furniture. While institutionalization and empowerment available resources be conducted by: a) an increase in quality of human resources , activities through training upon related government agencies; b ) the district government Jepara do specialised training for skilled craftsmen furniture , in which this institution specializes in handling about furniture designs .Factors that becomes obstacle to facilitate entrepreneurs furniture in Jepara among other: a )Limited raw materials. Needs raw materials wood to work a small scale and micro in Jepara regency is less than 99,27 m3 per year; b) Overall the the facility of the local government is help industry furniture, but in the facility in the form of capital there are certain conditions who makes IKM more choose not to take or receive capital assistance given by the government regional because they are considered convoluted; c) The appearance of competitors new: springing competitors, good in the domestic market and global; d) Certification And HaKI: provisions relating to the raw materials that environmentally friendly from certification institution international and lack of protection bar, resulting in a few items products furniture rejected some countries; e) Regeneration Human Resources, In terms of improving the quality of human resources skilled is very weak; and f) Marketing: access marketing both through products exhibition as well as through online media is very weak .Keywords: role of the government , facilitation industry furniture and free trade